Effect of Perceived Ease of Use, Promotion, and Trust on Fashion Product Purchasing Decisions Among Shopee PayLater Users in Sidoarjo - sintania fanissa; Alsaf Pebrianggara; Muhammad Yani (BIMA Journal (Business, Management, & Accounting Journal), 2026)
Purpose: This study aims to analyze the effect of perceived ease of use, promotion, and trust on fashion product purchasing decisions among Shopee PayLater users in Indonesia. Methodology: A quantitative research design was employed by distributing Likert-scale questionnaires to 140 Shopee PayLater users in the Sidoarjo area, selected through purposive sampling. The collected data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 3.0. Results: The results indicate that perceived ease of use has a positive and significant effect on purchasing decisions (T-statistic = 2.234; p-value = 0.026), promotion also shows a positive and significant effect (T-statistic = 6.398; p-value = 0.000), and trust significantly influences purchasing decisions (T-statistic = 2.640; p-value = 0.009). The R-square value of 0.959 demonstrates that perceived ease of use, promotion, and trust jointly explain 95.9% of the variance in purchasing decisions. Findings: The findings confirm that all three variables—perceived ease of use, promotion, and trust—serve as crucial determinants in shaping consumer purchasing behavior within the Buy Now Pay Later ecosystem, with promotion emerging as the most influential factor. Novelty & Originality: The novelty of this study lies in integrating behavioral and promotional factors within the context of Buy Now Pay Later (BNPL) services in fashion e-commerce, a relatively underexplored area in prior research. Its originality emerges from the empirical examination of these specific drivers in the Indonesian BNPL market, offering fresh insights into consumer decision-making processes in the rapidly growing digital payment landscape. Conclusions: These findings contribute theoretically to consumer behavior literature and practically provide insights for e-commerce platforms and fintech providers in formulating strategies to enhance purchasing decisions. Type of Paper: This paper is an empirical research paper.